Strategic supply chain management models - Petryk, I. (Видавництво Львівської політехніки, 2016)
The most used management models of supply chain were described in the article. The role of partnerships in the supply chain were clarified, models of the supply chain as an economic system characterized purpose of development, a set of parameters and initial results were analyzed. Areas of the overall impact of business processes as supply chain management parameters on the performance evaluation of the use of models were identified. Описано найбільш використовувані моделі управління ланцюгами поставок. Проаналізовано роль партнерства в мережі поставок, розроблено модель розвитку ланцюга поставок як економічної системи за сукупністю параметрів та вихідним результатом. Визначено межі загального впливу бізнес-процесів як параметрів управління ланцюгами поставок на основі оцінювання ефективності використання моделей.
Стратегічні моделі управління мережею поставок
Keywords: network organization; supply chain partnership; models of network development; JIT; MRP; мережеві організації; мережа поставок; партнерство; моделі розвитку мережі